2009
DOI: 10.1074/jbc.m807134200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tic110, a Channel-forming Protein at the Inner Envelope Membrane of Chloroplasts, Unveils a Response to Ca2+ and a Stromal Regulatory Disulfide Bridge

Abstract: Tic110 has been proposed to be a channel-forming protein at the inner envelope of chloroplasts whose function is essential for the import of proteins synthesized in the cytosol. Sequence features and topology determination experiments presently summarized suggest that Tic110 consists of six transmembrane helices. Its topology has been mapped by limited proteolysis experiments in combination with mass spectrometric determinations and cysteine modification analysis. Two hydrophobic transmembrane helices located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
117
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 55 publications
14
117
0
Order By: Relevance
“…As shown in Figure 2, CmTic110 is predicted to have a chloroplast-targeting transit peptide at its N terminus, followed by the two transmembrane helices agreed upon by both models (TM1 and TM2, Figure 2; shaded in yellow), and a large C-terminal region, similar to other Tic110s. As previously reported (Balsera et al, 2009), CmTic110 has similar secondary structure features to Tic110s from green plants except that it contains several insertions in the regions between TM2 and TM3, and between TM3 and TM4 of model 1. The C-terminal half Figure 2) conserved in all Tic110s (Kalanon and McFadden, 2008).…”
Section: Sequence Analyses Of Tic110 From Cyanidioschyzon Merolaesupporting
confidence: 53%
See 1 more Smart Citation
“…As shown in Figure 2, CmTic110 is predicted to have a chloroplast-targeting transit peptide at its N terminus, followed by the two transmembrane helices agreed upon by both models (TM1 and TM2, Figure 2; shaded in yellow), and a large C-terminal region, similar to other Tic110s. As previously reported (Balsera et al, 2009), CmTic110 has similar secondary structure features to Tic110s from green plants except that it contains several insertions in the regions between TM2 and TM3, and between TM3 and TM4 of model 1. The C-terminal half Figure 2) conserved in all Tic110s (Kalanon and McFadden, 2008).…”
Section: Sequence Analyses Of Tic110 From Cyanidioschyzon Merolaesupporting
confidence: 53%
“…The first model describes Tic110 with six transmembrane helices (herein referred to as TM1 to TM6; Figure 1a, model 1) located throughout the polypeptide. The first two transmembrane helices (TM1 and TM2) function as a signal-anchor sequence to target the protein to the inner membrane (L€ ubeck et al, 1997), and the rest of the polypeptide traverses the inner membrane four more times (TM3 to TM6) to form a Ca 2+ -sensitive and cation-selective channel (Heins et al, 2002;Balsera et al, 2009;Kovacs-Bogdan et al, 2011). Tic110 is therefore proposed to be the major channel for translocation of protein across the inner membrane.…”
Section: Introductionmentioning
confidence: 99%
“…These three proteins (Tic110, Tic40, and Hsp93) are thought to drive protein import into the stroma through repeated cycles of binding and release. Although an alternative model for the topology and function of Tic110 has also been proposed, in which Tic110 is a polytopic membrane protein that functions as a protein-conducting channel Balsera et al, 2009), a truncated version of Tic110 lacking the N-terminal transmembrane helices was shown to exist as a soluble protein when expressed in Escherichia coli or in the stroma of transgenic Arabidopsis (Inaba et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This notion was disputed in another study, where the reported Tic21 (Teng et al , 2006 ) most likely represents an ancient metal permease, which regulates iron uptake and metal homeostasis in chloroplast and not a protein conducting channel (Duy et al , 2007 ). Despite the occurrence of several proteinconducting channel candidates for the inner membrane of the chloroplast, considerable lines of evidence clearly pinpoint Tic110 as the central subunit of the TIC complex, forming a high-conductance cation-selective channel Balsera et al , 2009 ). Electrophysiology measurements indicate a pore size of 1.7 nm, similar to that of Toc75.…”
Section: The Tic Complex: a Short Glimpsementioning
confidence: 99%
“…After tranlocating through the outer envelope (OE), preproteins are imported either via Tic110 or Tic20 through the IE. Tic110 is thought to form a homodimer with a total of eight amphipathic transmembrane helices forming the translocation channel and four hydrophobic α -helices involved in the insertion into the membrane (Lubeck et al , 1996 ;Balsera et al , 2009 ). The proposed Tic20 channel is depicted as a homo-oligomer with a proposed molecular mass of > 700 kD but only three molecules are drawn for simplicity.…”
Section: Construction Underway: the Ambiguous Role Of Toc159 Family Amentioning
confidence: 99%